SAT0210 X-Ray and MRI Results from A Phase Iib Study of Subcutaneous Anti-Interleukin-6 Monoclonal Antibody Clazakizumab with or without MTX in Adults with Moderate-To-Severe Active RA and Inadequate Response to Conventional DMARDS Including Methotrexate. (10th June 2014) - Du, S.; Pellas, T.; van der Heijde, D.; Weinblatt, M.; Emery, P.; Zilberstein, M.; Conaghan, P.
Abstract : Background: Clazakizumab (CLZ) is a potent, neutralizing anti-interleukin (IL)-6 monoclonal antibody that is being studied in RA. CLZ in combination with MTX (+ MTX) or as monotherapy demonstrated efficacy in controlling the signs and symptoms of RA in a recent Phase IIb study. 1 In response to increasing interest in imaging techniques to supplement X-ray, magnetic resonance imaging (MRI) has emerged as a sensitive method of assessing treatment effect on joint damage in clinical trials of RA. MRI can demonstrate whether efficacy in improving signs and symptoms with treatment translates to tissue effects and non-progression in RA joints. Objectives: To assess the progression of joint damage by MRI at 12 weeks and X-ray at 24 weeks in a Phase IIb study of subcutaneous (SC) CLZ + MTX or as monotherapy compared with placebo + MTX or SC adalimumab (ADA) + MTX in patients with RA and inadequate response to DMARDs including MTX. Methods: Patients with moderate-to-severe RA and inadequate response to DMARDs, (including MTX) were randomized in a double-blind, double-dummy fashion to receive: placebo + MTX; CLZ 25, 100, or 200 mg + MTX; CLZ 100 or 200 mg monotherapy (every 4 weeks); or ADA 40 mg + MTX (every 2 weeks) for 24 weeks. The most swollen hand/wrist at baseline was imaged at both baseline and at Week 12 using 1.5T MRI with contrast enhancement and a phased-array knee coil. The MRI sequences were: 2D coronal short tau inversion recovery at pre-contrast, and 3D coronal isotropic T1 gradient-echo with fat suppression at pre- and post-contrast. MRI (n=322) was assessed using a modified version of the OMERACT RAMRIS criteria. 2 X-rays (n=351) of both hands/wrists and both feet was performed at baseline and Week 24 and assessed by modified Sharp/van der Heijde score (mTSS). Non-progressors were defined as patients with a change from baseline ≤0. Results: The proportion of MRI non-progressors at Week 12 was numerically greater in the CLZ + MTX groups vs MTX alone for all components (Table). At Week 24, the proportion of X-ray non-progressors was numerically higher for all CLZ arms compared with MTX by mTSS and its components. Favourable trends in the mean change from baseline in MRI components and X-ray mTSS scores and erosion were observed in the CLZ + MTX arms versus MTX alone. In a post hoc analysis, combining all CLZ + MTX treatment arms led to a mean change from baseline (95% CI) in mTSS of 0.2 (–0.3, 0.6) versus 1.8 (0.9, 2.6) in the MTX arm (p<0.001). Conclusions: Clazakizumab in combination with MTX demonstrated reduced progression of joint damage by MRI as early as 12 weeks and by X-ray after 24 weeks. Larger trials with clazakizumab in RA are warranted to confirm these findings. References: Weinblatt M et al. Arthritis Rheum 2013;65:S735-6. Ostergaard M et al. Ann Rheum Dis 2005;64:3–7 Disclosure of Interest: S. Du Shareholder of: BMS, Employee of: BMS, T. Pellas Shareholder of: BMS, Employee of: BMS, D. van der Heijde Consultant for: AbbVie, Amgen, AstraZeneca, Augurex, BMS, Celgene, Centocor, Chugai, Covagen, Daiichi, Eli-Lilly, GSK, Janssen Biologics, Merck, Novartis, Novo-Nordisk, Otsuka, Pfizer, Roche, Sanofi-Aventis, Schering-Plough, UCB, Vertex, M. Weinblatt Grant/research support: BMS, Crescendo Bioscience, UCB, Consultant for: BMS, Crescendo Bioscience, UCB, Abbvie, Roche, Janssen, P. Emery Grant/research support: AbbVie, BMS, Merck, Pfizer, Roche, Consultant for: AbbVie, BMS, Merck, Pfizer, Roche, Takeda, M. Zilberstein Employee of: BMS, P. Conaghan Speakers bureau: AbbVie, BMS, Janssen, Pfizer, Roche, UCB DOI: 10.1136/annrheumdis-2014-eular.1102